Stakeholders’ perception of factors influencing adoption of a pediatric weight management intervention: a qualitative study - Sierra-Velez, Desiree; Gundewar, Anisha; Persaud, Alicia; Simione, Meg; Castro, Ines; Perkins, Meghan; Lindros, Jeanne; Salmon, Jeremiah; Smith, Justin D.; Taveras, Elsie M.; Fiechtner, Lauren (Frontiers in Public Health, 2023)
Childhood obesity is highly prevalent in the US and disproportionately impacts communities of color and low-income populations; these disparities have worsened during the COVID-19 pandemic. Adoption of effective pediatric weight management interventions (PWMIs) that have been evaluated among low-income diverse populations is needed. The Healthy Weight Clinic PWMI, a package co-developed by the American Academy of Pediatrics and Massachusetts General Hospital, helps health centers establish multidisciplinary Healthy Weight Clinics based on previous randomized controlled trials which demonstrated effectiveness. We sought to identify the factors influencing successful adoption of this PWMI and understand adaptations needed prior to implementation in new sites.